Guardian angel - Muchamore, Robert (London : Hodder Children's Book, a division of Hachette Children's Books, 2013)
While undercover, Ryan, an agent for a secret organization of child spies who has saved Ethan's life multiple times, wonders if he can destroy Ethan's family-run criminal empire without hurting Ethan.
Originally published: 2012.
Young Adult.
Young Adult
Keywords: Teenagers -- Juvenile fiction; Spies -- Fiction; Teenagers -- Fiction; Spy stories; Teenagers -- Fiction; Spy stories